Evaluating performance of hybrid PCM-fan and hybrid PCM-desiccant vests in moderate and hot climates. (March 2019) - Itani, Mariam; Bachnak, Rana; Ghaddar, Nesreen; Ghali, Kamel
Abstract: Personal cooling vests containing phase change material (PCM) are commonly used for outdoor workers. They cool the human torso and provide a better rating of overall thermal comfort in hot environments. However, PCM cooling vests become less effective at conditions where a high sweat secretion is present, and at very humid or very dry ambient conditions. Therefore, design variations have been used to justify the use of the PCM cooling vest in such conditions. These mainly include the hybrid PCM-Desiccant cooling vest, containing thin solid desiccant packets attached to the PCM packets, and the hybrid PCM-Fan vest, formed of PCM packets and ventilation fans. The aim of this study is to develop criteria for comparing the performance of the three vests at different ambient conditions and human metabolic rates. The comparison used predicted values of torso skin temperature and overall thermal comfort using validated simulation models for heat and mass transfer in each of the vest layers, integrated with a validated bio-heat model. Steady state results were obtained at metabolic rates of 3 and 6 MET at ambient temperatures of 35, 40 and 45 °C with varying relative humidity ( RH ). Based on developed criteria, it was found that the use of the PCM-only vest is recommended at activity level of 3 MET in moderate ambient temperature of 35 °C and at ambient RH of 17% and 27%. At the higher ambient temperatures of 40 °C and 45 °C and low ambient RH, the use of the hybrid PCM-Fan vest is recommended. However, at moderate RH both hybrid vest types can be used while at higher ambient RHs, the use of hybrid PCM-Desiccant vest is justified. Similarly, it was shown that at higher metabolic rate of 6 MET, both hybrid vests can be used at moderate RH . However, at high RH, the hybrid PCM- Desiccant vest is recommended. Graphical abstract: Schematic of the side back view of each of (a) the PCM-only cooling vest, (b) the hybrid PCM-Desiccant cooling vest and (c) the hybrid PCM-Fan cooling vest. Plots of the steady state overall thermal comfort at 35 °C at 3 MET. fx1 Highlights: A performance criteria to compare effectiveness of different cooling vests was developed. Integrated PCM-only and hybrid vest models with a bioheat model were utilized. Steady-state predictions of heat losses, torso temperatures and thermal comfort were predicted. Using PCM-only vest at 3 MET, Tamb of 35 °C and RH of 17% and 27% is appropriate. Both hybrid vests at 40 and 45 °C and moderate RH are suitable, while at higher RH use PCM-Desiccant.